The median lethal dose (LD50) of acetylcholine in guinea pigs native of Lima and La Oroya - Barreda Bebin, Alfredo (1957)
The problem of man and animals, who live in locations several thousand meters above sea level and with multiple different to coastal biological peculiarities in different aspects, has attracted our attention, and this primarily due to the interest aroused us teachers Mongo and Carlos Alberto Hurtado et al, showing the full reality of the issue and the importance of their study in a country like ours, where most people live in these places.